Urban decay and traffic load on highway in Nigeria: a study of Ibadan-Oyo road (2023)
This study investigates traffic load as a cause of urban decay and failure on a highway in Nigeria, using Ibadan-Oyo road as a case study. This study identifies road failure as a major city nightmare that affects the well-being of urban dwellers in the study area. The Ibadan-Oyo road is a segment of the major road intersection that connects the southern part of Nigeria with the north. The methodology for this study involves a well-structured questionnaire administered to road users to elicit primary data on the factors and effects of urban decay due to traffic load. A total of 100 Questionnaires were randomly distributed among the road users (vehicular and pedestrians) of the Ibadan-Oyo road. In all, 92 questionnaires were returned. These were analyzed using the Relative Importance Index (R.I.I) and basic statistical tools, to better understand the trend of responses. The results from the study show the factors that enable traffic load and failure include the road as a major route to various parts of the country, not obeying driving laws, poor driving habits, and poor/absence of road pavements. The stress of heavy vehicles on the Ibadan-Oyo road also proves to be a major factor which leads to incessant failure of the road, even after maintenance or reconstruction has been carried out. The failure of this urban infrastructure and the poor road networks leads to many accidents, acute vehicular fuel consumption, waste of time, breakdown of vehicles and road rage. To drastically reduce the impact of infrastructural decay and failure on highways, this study suggests the following: construction of separate routes for trucks and other heavy vehicles, provision of various parks along travel routes for heavy vehicles, and use of a weighing bridge to regulate the range of axle load, replacement of flexible paving with a more rigid design for increased strength and road life span, proper rehabilitation and reconstruction of the failed segment, provision of an alternate railway system to convey heavy goods and also reduce the stress on road transport, in-depth training of vehicle drivers and traffic personnel and lastly, enlargement of the road width.